Edukasi dan Praktikum Enterpreneurship Untuk Teruna-Teruni Terdampak Covid-19 Di Desa Padangkeling - Luh Gede Kusuma Dewi; Nyoman Ayu Wulan Trisna Dewi (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Youngsters in Padangkeling Village are residents who also feel the impact of the Covid-19 pandemic, of which more than 25% of the youngsters have lost their work relationship since 2020. Through the community service program which is part of the Tridarma of Higher Education, lecturers and students who experienced in entrepreneurship providing education and entrepreneurship practicum for youngsters i who are experiencing the impact of the COVID-19 pandemic in Padangkeling Village, Buleleng Regency. This is a form of concrete action that can be carried out by academics as a solution to problems in society. This program is carried out for two days. The education provided is entrepreneurship materials and business plans. Students who already have businesses also share their experiences in the business world. The success of this activity can be measured by the increase in participants' knowledge before and after the presentation of the material, and the ability of participants to develop their own business ideas.